2011
DOI: 10.4314/gmj.v45i1.68922
|View full text |Cite
|
Sign up to set email alerts
|

Kawasaki disease in Ghana: Case reports from Korle Bu Teaching Hospital

Abstract: Kawasaki disease, an acute febrile vasculitis, predominantly affects children under the age of 5 years and is thought to be a rare disease in the developing world. It has previously never been reported in Ghana. We report 3 cases from February, 2007 to February, 2008. This potentially serious disease has no definitive diagnostic test and it is not unusual for diagnosis to be delayed with serious consequences. Any child with irritability and persisting fever (>5 days) not responding to antipyretics and antibiot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 10 publications
1
8
1
Order By: Relevance
“…KD is generally a disease of the young, with 80% of cases occurring in children less than 5 years 4 . Unlike Sotimehin et al in Nigeria and Badoe et al in Ghana who reported KD in 3 and 4 year old children respectively 8,9 , our patient presented at an unusual age of 14years. A few other reports across the world have also reported KD among atypical age group 10,11 .…”
Section: Enlarged Cervical Lymph Nodescontrasting
confidence: 77%
See 1 more Smart Citation
“…KD is generally a disease of the young, with 80% of cases occurring in children less than 5 years 4 . Unlike Sotimehin et al in Nigeria and Badoe et al in Ghana who reported KD in 3 and 4 year old children respectively 8,9 , our patient presented at an unusual age of 14years. A few other reports across the world have also reported KD among atypical age group 10,11 .…”
Section: Enlarged Cervical Lymph Nodescontrasting
confidence: 77%
“…Renal involvement is rare, but has been reported [5][6][7] . It can manifests with proteinuria, hematuria or even frank renal failure 1, 5-7. There are only few reports of KD in Africa including Nigeria and almost all were among children within the typical age group 8,9 . Occurrence in adult and older pediatric age group is rare 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Both cases described above presented to us after a prolonged duration of fever and failure to respond to antimalarials and antibiotics. This is a common presentation also described in case reports from Ghana [ 3 ].…”
Section: Discussionsupporting
confidence: 59%
“…In Africa, two cases were reported in South Africa in Caucasian children in 1980 but the first case in an African child was reported in Ivory Coast in 1981. Despite of sporadic cases being reported across many countries in Africa, mainly North Africa and the West African region, the epidemiological data for KD is limited for African countries [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, Agha et al reported two cases with incomplete KD in children < 5 years old complicated with coronary aneurysm [35]. The data for KD incidence are lacking in sub-Saharan Africa, however several sporadic cases have been reported across many countries in the region [36]. These findings raise the possibility that KD is not that uncommon in the Middle East and sub-Saharan Africa as previously thought, and increased awareness and diagnosis may reveal the true incidence of KD.…”
Section: Kd In the Middle East And Sub-saharan Africamentioning
confidence: 95%